2006
DOI: 10.1093/humrep/del395
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovaries after precocious pubarche: relation to prenatal growth

Abstract: The presence of a PCO morphology in women with a PP history was found to relate to prenatal growth. It would be of interest to verify whether a similar relationship exists in anovulatory and/or hyperandrogenic women without PP history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…However, the number of cases was very small (cases/ controls: 12/12). In contrast, Ibáñez et al [40] showed that women with a history of PA (mean age 28 ± 2 years) have an elevated CIMT compared to age-matched controls. Similarly, we showed that CIMT levels were significantly different in children with PA at diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…However, the number of cases was very small (cases/ controls: 12/12). In contrast, Ibáñez et al [40] showed that women with a history of PA (mean age 28 ± 2 years) have an elevated CIMT compared to age-matched controls. Similarly, we showed that CIMT levels were significantly different in children with PA at diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…However, the association was with high birthweight, which was associated with hirsute women with polycystic ovaries who had higher than normal ovarian secretion of androgens (31). Another group in Spain has studied adolescent girls, primarily with premature pubarche, and has consistently found that low birthweight is associated with more severe reproductive and metabolic abnormalities (11,12,(32)(33)(34). Furthermore, these investigators have shown an inverse association between birthweight and ovarian volume, which persists even after excluding those with polycystic ovary morphology (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…First, prenatal exposure to androgens can produce a phenocopy of PCOS in rhesus macaques, sheep and rodents (6 -8), and humans (9,10). Second, several studies in humans have suggested that there is an association between low birthweight and features of PCOS (11)(12)(13). The human studies, however, have been limited by small sample size, incomplete reproductive or metabolic phenotyping, and the lack of family-based comparison groups.…”
mentioning
confidence: 99%
“…IUGR followed by catch up growth during childhood increases the risk of precocious pubarche (Ibanez et al 1998a), anovulation PCOS (Ibanez et al 2002b(Ibanez et al , 2007, and characteristics of the metabolic syndrome in adolescence (Ibanez et al 2006a). Insulin resistance has been suggested to be a central driver in these associations and treatment with insulin sensitizers in girls with precocious pubarche has been shown to significantly delay the onset of early menarche in this population (Ibanez et al 2006b(Ibanez et al , 2008a.…”
Section: Establishment Of Female Reproductive Function: a Brief Overviewmentioning
confidence: 99%
“…Although it is clear that intrauterine factors play a significant role in the development of the female reproductive system and the risk of dysfunction later in life (de Zegher & Ibanez 2006, Ibanez et al 2007, Melo et al 2010, Franks & Berga 2011, the causal factors are not still clearly defined (Cresswell et al 1997). In a small population of girls, SGA was associated with an increased risk of developing PCOS (Ibanez et al 1998a(Ibanez et al ,b, 2001(Ibanez et al , 2008b.…”
Section: Establishment Of Female Reproductive Function: a Brief Overviewmentioning
confidence: 99%